Strategy of The Service of Cooperatives and UKM Province of Sumsel Province in The Development of the Micro, Small and Medium Business Sector (UMKM) During The Covid-19 Pandemic - Choiriyah Choiriyah; Saprida Saprida; Emilia Sari (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
The Covid-19 pandemic has had an impact on economic instability, including Micro, Small, and Medium Enterprises (UMKM). In general, the majority of UMKMs experienced a decline in income and even went bankrupt due to the Covid-19 pandemic. Facing this, a strategy is needed for UMKMs to survive and be able to develop their business amid the Covid-19 pandemic. One of the main aspects that have an impact on UMKM actors is the decline in the number of sales which makes UMKMs' financial condition in a crisis. Restrictions on social activities make it difficult for UMKMs to move to develop a business scale if they only use these conventional methods. Business actors have taken various ways to respond to these difficult conditions to maintain their business. The lack of mass mobility around the market certainly hampers the promotion rate which affects the level of sales. Overcoming this, online marketing through the media is the right step that must be taken by business actors.Keywords: Strategy; Department of Cooperatives; UKM; Development of The Micro; Small and Medium Enterprise (Umkm) Sector; During The Covid-19 Pandemic AbstrakPandemi Covid-19 memberi dampak pada ketidakstabilan ekonomi, termasuk Usaha Mikro Kecil Menengah (UMKM). Secara umum, mayoritas dari pelaku UMKM mengalami penurunan pendapatan bahkan kebankrutan akibat pandemi Covid-19. Menghadapi hal demikian diperlukan strategi bagi UMKM untuk tetap bertahan dan dapat mengembangkan bisnisnya di tengah pandemi Covid-19. Aspek utama yang sangat berdampak bagi pelaku UMKM salah satunya adalah penurunan jumlah penjualan yang membuat kondisi keuangan UMKM dalam kondisi krisis. Pembatasan kegiatan sosial membuat UMKM sulit untuk bergerak mengembangkan skala usaha jika hanya memanfaatkan metode konvensional tersebut. Pelaku usaha telah melakukan berbagai cara merespon kondisi sulit ini untuk mempertahankan usahanya. Kurangnya mobilitas massa di sekitar pasar tentu menghambat laju promosi yang berpengaruh kepada tingkat penjualan. Mengatasi hal tersebut, pemasaran secara online melalui media merupakan langkah tepat yang harus dilakukan oleh para pelaku usaha.Kata Kunci: Strategi; Dinas Koperasi; UKM; Pengembangan Sector Usaha Mikro Kecil dan Menengah (UMKM); Masa Pandemic Covid-19